Respostas
respondido por:
4
Olá!!
Vamos usar a fórmula >>> Sn = A1(qⁿ-1)
------------
q-1
3280 = 1(3ⁿ-1)
---------------
2
3280.2 = 3ⁿ-1
6560 = 3ⁿ-1
3ⁿ = 6561
3ⁿ = 3⁸
n = 8 <<< Resposta
Vamos usar a fórmula >>> Sn = A1(qⁿ-1)
------------
q-1
3280 = 1(3ⁿ-1)
---------------
2
3280.2 = 3ⁿ-1
6560 = 3ⁿ-1
3ⁿ = 6561
3ⁿ = 3⁸
n = 8 <<< Resposta
respondido por:
0
resolução!
q = a2/a1
q = 3/1
q = 3
Sn = a1 ( q^n - 1 ) / q - 1
3280 = 1 ( 3^n - 1 ) / 3 - 1
3280 = 1 ( 3^n - 1 ) / 2
6560 = 3^n - 1
6560 + 1 = 3^n
6561 = 3^n
3^8 = 3^n
n = 8 termos
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás